The Greening of American Catholicism: Identity, Conversion, and Continuity - Warner, Keith Douglass (Religion and American culture, 2008)
Environmental concern is emerging in all major American religious denominations, a process known as the “greening of religion.” The dynamics of a greening process illustrate how individuals incorporate emergent social concerns into their existing moral worldviews and show the ways in which religious identities shape that process. Analyzing the dynamics of this phenomenon reveals much about how a community understands the meaning of religious conversion, demonstrates the stability of religious identities, and illustrates how leaders use new problems to reframe religious identities. The greening of American Catholicism builds upon prior efforts to extend a practical theology of social justice (conversion) but articulates new moral responsibilities for future generations while reinforcing identity (continuity). Pope John Paul II opened a new domain for Catholic social teaching by his numerous teachings about environmental stewardship. U.S. Catholic greening efforts built organically upon the Catholic social teaching initiatives of the 1980s, addressing peace and economic justice, and the emergence of what some refer to as a “distinctly Catholic” contribution to environmental ethics should be interpreted in light of these efforts. This term is not precisely defined, but it suggests a concern for cultivating environmental values within the framework of a Catholic identity and for not subverting Catholic religious identity to conventional “secular” environmental values. The rhetorical framing of environment concerns by an ethic of justice was drawn from the biblical vision of justice, but it was influenced by the American environmental justice movement that emerged during this period. The most innovative expression of the greening of American Catholicism has been a set of regional initiatives, bringing Catholic social vision to bear on local issues through lay civic engagement. The lessons from this study speak to the broad evolution of religious environmental ethics in American culture and can inform future studies of this transreligious phenomenon.